2012
DOI: 10.3892/mmr.2012.1110
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 activates the P13K/AKT signaling pathway via upregulation of secretory clusterin

Abstract: Abstract. Secretory clusterin (sCLU) is a type of stressinduced, pro-survival glycoprotein elevated in early-stage cancer. It enhances cancer cell survival and is associated with several types of cancer progression. In this study, we measured the PI3K/AKT signaling activity by determining the phosphorylation level of the AKT protein, namely pAKT. A549 human non-small cell lung carcinoma (NSCLC) cells were treated with insulin-like growth factor-1 (IGF-1) for various periods of time.The results showed that IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 43 publications
(43 reference statements)
2
36
0
Order By: Relevance
“…This suggests that IGF-1 stimulates the PI3K/Akt signaling pathway, and is consistent with the work of others [44]. It is very likely that inhibition of IGF-1 leads to down-regulation in expression of the MHC-1 antigen processing [45].…”
Section: Discussion and Summarysupporting
confidence: 90%
“…This suggests that IGF-1 stimulates the PI3K/Akt signaling pathway, and is consistent with the work of others [44]. It is very likely that inhibition of IGF-1 leads to down-regulation in expression of the MHC-1 antigen processing [45].…”
Section: Discussion and Summarysupporting
confidence: 90%
“…PI3K/AKT and ERK1/2 is believed to act downstream of sCLU [16,17,34,35,36]. In this study, DDP could up-regulate the expression of sCLU, which is correlated with the activation of pAKT and pERK1/2.…”
Section: Discussionmentioning
confidence: 56%
“…We therefore suggested ERK1/2 signalling is regulated by clusterin. Many studies in literature have reported that AKT pathway may also regulated by clusterin in cancers including lung cancer [17,35,36]. …”
Section: Introductionmentioning
confidence: 99%
“…However, Bcl-2 suppression is a p53-independent effect, such that knockdown of p53 only minimally suppressed cell death, but a pan-caspase inhibitor completely avoided cell death. Another mechanism involved in sCLU prosurvival activity is the upregulation of the phosphatidylinositol 3- kinase (PI3K)/protein kinase B (AKT) pathway15 and insulin-like growth factor (IGF)-1 activates the PI3K/AKT pathway through upregulation of sCLU 16…”
Section: Clusterin Actionsmentioning
confidence: 99%